P‐Chirogenic Triazole‐Based Phosphine: Synthesis, Coordination Chemistry, and Asymmetric Catalysis. Issue 30 (16th July 2020) - Bayardon, Jérôme; Rousselle, Benjamin; Rousselin, Yoann; Bonnin, Quentin; Malacea‐Kabbara, Raluca
Abstract : Herein we report the synthesis of a new P‐chirogenic triazole‐based phosphine according to the ephedrine methodology. Upon reaction with late transition‐metal derivatives, Rh I and Pd II, phosphine‐triazole forms complexes with bidentate P, N coordination, as demonstrated by spectroscopic and X‐ray crystallographic analyses. First experiments in asymmetric catalysis showed the catalytic potential of this new chiral P, N‐type ligand. Abstract : The stereoselective synthesis of a novel P‐chirogenic triazole‐based phosphine was achieved. Its coordination to transition‐metals was explored, and a P, N‐chelation mode was demonstrated. Application to this chiral phosphine as ligand in asymmetric catalysis is also reported.